M-Agriculture recording system for milk producers in Kenya: a case of Uasin Gishu County - Limo, Richard Kipchirchir (Strathmore University, 2017)
Managing milk production efficiently is a key factor to the development of the dairy industry in Kenya. The availability of milk production information is a major challenge when it comes to management which has led to a number of trials by the Kenya dairy board (KDB) to standardize milk recording. The milk recording schemes have not been successful due to various factors such as cost of implementation, technology limitations, time constraints, the large number of small scale farmers and the education levels of the farmers. This means that information that can be used for management, analysis and even prediction is more or less nonexistent. The standardization of milk recording in developed countries engineered by the International Committee for Animal Recording (ICAR), has seen huge developments in the dairy industry of the member countries. This shows the positive effect in the good management practices that should be emulated by the developing countries such as Kenya. Although technological advancement can be viewed as a constraint, studies have shown otherwise with increase in adoption of technologies in the developing countries such as mobile phone technology. In Kenya there has been a steady increase of mobile subscribers which has penetrated to even the remote parts of the country. This growth has largely been due to ground breaking innovations e.g. mobile money transfer which has seen more people depend on mobile phone services for their daily activities. Kenya is seeing more and more mobile phone related innovations in various economic sectors, agriculture included. M-agriculture which is the use of mobile phone technology in agriculture including the dairy sector, can be used to solve the problems such as milk management. Using M-agriculture as a solution to milk recording in Kenya can enable standardization and create availability of milk production information for management, analysis and even prediction. This thesis focuses in developing an M-agriculture data collection system for the dairy farmers which provides a solution for management as well as curation of the much needed milk production information for the dairy industry.
Thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Information Technology (MSIT) at Strathmore University
Keywords: M-agriculture; MobiCrop; Enterprise Mobile Service Architecture; M-Kulima Model; Milk Recording